1998
DOI: 10.1038/nm0898-949
|View full text |Cite
|
Sign up to set email alerts
|

DNA immunization protects nonhuman primates against rabies virus

Abstract: More than 40,000 people die annually from rabies worldwide. Most of these fatalities occur in developing countries, where rabies is endemic, public health resources are inadequate and there is limited access to preventive treatment. Because of the high cost of vaccines derived from cell culture, many countries still use vaccines produced in sheep, goat or suckling mouse brain. The stability and low cost for mass production of DNA vaccines would make them ideal for use in developing countries. To investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(49 citation statements)
references
References 16 publications
1
45
0
3
Order By: Relevance
“…Langerhans cells) of the viable epidermis [19,20]. Since the earliest DNA vaccine studies, direct comparisons of PMED to needle-based approaches for DNA vaccine delivery in mice [21][22][23][24][25][26][27] and monkeys [28][29][30][31] have shown that PMED can induce higher antibody and/or CD8 + T cell responses with substantially lower doses (100-1000-fold) of DNA. The eVectiveness of this system is likely related to the use of a delivery technology that deposits DNA directly into cells [18,20] as well as the immune competence of the epidermis as a delivery site [32,33].…”
Section: Particle-mediated Epidermal Delivery Of Dna Vaccinesmentioning
confidence: 99%
See 4 more Smart Citations
“…Langerhans cells) of the viable epidermis [19,20]. Since the earliest DNA vaccine studies, direct comparisons of PMED to needle-based approaches for DNA vaccine delivery in mice [21][22][23][24][25][26][27] and monkeys [28][29][30][31] have shown that PMED can induce higher antibody and/or CD8 + T cell responses with substantially lower doses (100-1000-fold) of DNA. The eVectiveness of this system is likely related to the use of a delivery technology that deposits DNA directly into cells [18,20] as well as the immune competence of the epidermis as a delivery site [32,33].…”
Section: Particle-mediated Epidermal Delivery Of Dna Vaccinesmentioning
confidence: 99%
“…However, optimization of the delivery device [37], vaccine vectors [38], and immunization regimens [26,38] substantially improved this technology so that later studies employing a clinical research device achieved robust and protective levels of immunity in nonhuman primates after only 1-3 doses [29,30,39,40]. Recent studies have shown that the delivery device employed can inXuence the immunogenicity of PMED in nonhuman primates.…”
Section: Optimization Of Pmed In Large Animal Preclinical Modelsmentioning
confidence: 99%
See 3 more Smart Citations